INFLUENCE OF INCLUSIVENESS ON PROMOTION OF CHILD-FRIENDLY SCHOOLS’ MODEL IN PUBLIC PRIMARY SCHOOLS IN MERU COUNTY, KENYA - Munene, Gichobi, Peter; Severina, Dr. Mwirichia; Lucy, Dr. Ikiara (IJRDO- Journal of Educational Research, 2022)
Inclusiveness in education should foster acceptance, kindness and considerate regard for all leaners, and attending to diverse learning needs, as well as addressing gender-based and disability related stereotypes. The study therefore sought to establish the influence of inclusiveness on promotion of child-friendly schools’ model in public primary schools in Meru county, Kenya. The study was anchored in Katz & Kahn’s (1978) systems theory and transformational leadership theory (Burns, 1978). Correlational research design with a mixed methods approach was used. The study targeted 6,814 persons, including 5520 teachers, 647 representatives of boards of management and 647 school heads from the entire county. The study utilized Yamane’s technique to compute a sample of 378 participants. Quantitative data was collected from teachers and headteachers through a self-designed questionnaire with closed-ended items. Interview guide with open-ended items was used to gather qualitative information from representatives of boards of management. Piloting of instruments was conducted with information from 40 individuals, comprising of 24 teachers, 8 representatives of boards of management, and 8 headteachers, who were not part of the main study. Cronbach’s alpha was used to determine the reliability of instrument. A measure of 0.71 was achieved, indicating high internal consistency. Quantitative data was analyzed in descriptive and inferential statistics, while qualitative data was analyzed in thematic analysis. The findings indicated that inclusiveness had statistically significant influence on promotion of CFS model (r (286) = 0.18. p< 0.05). The study recommends that school-based support programmes aimed at promoting fairness, and cushioning learners from poor socioeconomic backgrounds be replicated in all schools. This could be achieved through creation of school-based income generating activities, incorporation of external stakeholders such as alumni associations, and donor funding.